Arbeit an der Kultur : Margaret Mead, Gregory Bateson und die amerikanische Anthropologie, 1930-1950 - Neidhöfer, Thilo (2021)
This story of an extraordinary marriage of an intellectual couple shows how the private became scientific and science became political.